(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
This article establishes the continuities that exist between symbolism and surrealism through their representations—in spite of the stated ruptures. It also identifies the overlap between the two cultural centers of Lima and Paris at the turn of the century and determines their critical effects on the concepts of influence, national culture, and cosmopolitanism.